Epidemiological Study on Factor VII, Factor VIII and Fibrinogen in an Industrial Population - II. Baseline Data on the Relation to Blood Pressure, Blood Glucose, Uric Acid, and Lipid Fractions - Balleisen, L; Assmann, G; Bailey, J; Epping, P-H; Schulte, H; van de Loo, J (Thrombosis and Haemostasis, 1985)
In a preceding paper the baseline data in the Munster Arteriosclerosis Study (PROCAM study) of the levels of fibrinogen, factor VIIc and factor VIIIc were described, and their correlation of age, body weight, smoking, alcohol, pill-using and menopause discussed. In this part the relationship of these coagulation factors to blood pressure, blood glucose, uric acid and lipid parameters, which were examined in 4186 apparently healthy individuals, is presented. The correlations are described using two different statistical models, first the Pearson correlation coefficients after allowing each clotting factor for the effects of age, cigarette and alcohol consumption, body weight, menopausal state, pill using and the other clotting factors, and secondly by a multiple regression analysis. The data suggest that there are multiple interrelationships between hemostatic factors and the variables under consideration. The most striking positive correlations were found for factor VII c to blood glucose and triglycerides in men and women and to HDDcholesterol in women.
Keywords: Factor VII; factor VIII; Fibrinogen; Epidemiology